EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK RESTORAN TERHADAP PAJAK DAERAH KOTA BANJARMASIN TAHUN 2016-2019 - Tri Rayyan Noor Rahmat; Norlena (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2020)
The purpose of the research is basically to find out more: (1) How Effective and Contribution of Restaurant Tax Revenue is to Regional Taxes for 2016-2019. (2) What is the level of realization targeted by the Banjarmasin City Regional Finance Agency during the receipt of Restaurant Tax for 2016-2019 Regional Taxes. (3) Obstacles faced by the Banjarmasin City Regional Finance Agency